Evolution of vision reducing cataract in skin smear positive lepromatous patients: does it have an inflammatory basis?. Issue 8 (14th February 2007) - Daniel, Ebenezer; Sundar Rao, P S S
Abstract : Aim: To describe the incidence and risk factors of vision reducing cataract in skin smear positive lepromatous patients. Methods: Prospective longitudinal cohort study: 212 newly diagnosed lepromatous patients were followed during the two years of treatment with multidrug therapy and for a further five years, with biannual ocular examinations. Incidence of vision reducing (⩽6/18) cataract was calculated as the number of patients with cataract per person year of cataract-free follow up among those who did not have cataract at baseline. Results: Cataract was present in 27 (11%) of lepromatous patients at diagnosis. Forty nine patients (2.87%/person year (95% confidence interval (CI), 2.17% to 3.80%)) developed cataract during a total follow up period of 1704 person years; 45 of these were ⩾41 years old and were followed for a total of 638 person years with an incident rate of 0.070 (95% CI, 0.0523 to 0.094). Stepwise multiple regression confirmed the association of age (per decade) (hazard ratio (HR) = 2.50 (95% CI, 1.82 to 2.78), p<0.001), clofazimine crystals on the cornea (HR = 49.92 (5.48 to 454.82), p = 0.001), grade 2 deformity in all limbs (HR = 3.17 (1.12 to 8.97), p = 0.029), and uveal inflammation (HR = 3.52 (1.42 to 8.67), p = 0.006). No significant association was found with oral steroids. Conclusions: Cataract develops at the rate of 7%/person year in lepromatous patients over 40 years of age. It is associated with increasing age, subclinical intraocular inflammation, and grade 2 deformity.